The Public Broadcaster And The Dynamics Of The Romanian Radio Market - Davian Vlad (Social Sciences and Education Research Review, 2016)
The permanent changing of the listening habits of the population and the rapid technological evolution represent a real challenge for the Romanian public radio. That is the reason why the editorial management of the public broadcaster should find the proper strategy to keep up with the transformations constantly taking place in the domestic radio market. Adapting to the New Media paradigm is a vital matter to any radio station, including the public one. Therefor the modern ways of reaching more audience should be a priority for the management of the public broadcaster, especially when the dynamics of the radio market are often spectacular and rather unpredictable. That is why the editorial strategy of the public radio must focus on the constant improvement of both the editorial offer and the means of transmission. The "battle" for rating and market share can be won only by constant adjusting and readjusting the policy of the radio station and by permanently improving the structure and the content of the radio programs.